Retrospective Analysis of Clinical Attributes Related to Uterine Torsion in Goats - Baria, Vishnu R.; Chauhan, Prakash M; Suthar, Babulal N; Patel, Ramesh M; Prajapati, Ankit S (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The retrospective analysis of clinical attributes and incidence of uterine torsion was worked out from the last ten year’s records, 2012-21, maintained at the Veterinary Clinical Complex of the institute. The overall incidence of uterine torsion was 14.17 %, with a higher occurrence in pluriparous (63.89%) compared to primiparous goats (36.11%). The majority of goats suffered from post-cervical torsion (77.78%) than that of pre-cervical torsion (22.22%), whereas the degree of torsion, 180 vis-a-vis direction of uterine rotation either to the right or left, distributed equally. Goat-carried single kids (97.22%) had significantly (P
Keywords: Goat; Retrospective; Uterine torsion